2003
DOI: 10.1021/ic034388l
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Dinuclear, Macrocyclic, and Chain Structures from HgI2 and a Semirigid Benzimidazole-Based Bridging Ligand:  An Example of Ring-Opening Supramolecular Isomerism

Abstract: The reactions of HgI(2) with the semirigid ditopic ligand 1,3-bis(benzimidazol-1-ylmethyl)-2,4,6-trimethylbenzene (bbimms) afforded three new complexes, [Hg(2)(mu-I)(2)I(2)(bbimms)] (1), [Hg(2)I(4)(bbimms)(2)] (2), and catena-poly[HgI(2)(bbimms)] (3). The ligand and all complexes have been structurally characterized by single-crystal X-ray diffraction. 1 is a triply bridged dinuclear complex comprised of two Hg(II) ions, one bridging ligand, two bridging I(-) anions, and two terminal I(-) anions. 2 is a dinucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(47 citation statements)
references
References 29 publications
1
46
0
Order By: Relevance
“…A literature survey of mercury halide complexes with benzimidazole derivatives has shown that they come in two main types: polymeric, bridging either through the halide (Zhang et al, 2015;Li et al, 2007;Shen et al, 2005) or through alternative N atoms from the benzimidazole moieties (Xiao et ISSN 2056-9890 al., 2009Huang et al, 2006;Li et al, 2007Li et al, , 2012aDey et al, 2013;Du et al, 2011;Chen et al, 2013;Su et al, 2003;Xu et al, 2011), or as discrete molecules (i.e. non-polymeric).…”
Section: Chemical Contextmentioning
confidence: 99%
“…A literature survey of mercury halide complexes with benzimidazole derivatives has shown that they come in two main types: polymeric, bridging either through the halide (Zhang et al, 2015;Li et al, 2007;Shen et al, 2005) or through alternative N atoms from the benzimidazole moieties (Xiao et ISSN 2056-9890 al., 2009Huang et al, 2006;Li et al, 2007Li et al, , 2012aDey et al, 2013;Du et al, 2011;Chen et al, 2013;Su et al, 2003;Xu et al, 2011), or as discrete molecules (i.e. non-polymeric).…”
Section: Chemical Contextmentioning
confidence: 99%
“…Though Hg···Hg distance as short as 3.41Å has never been reported but many halide bridged Hg based structures, with ubiquitous Hg 2 X 2 bridges are known to have Hg···Hg inetarctions within this range. [133][134][135][136][137][138][139][140] However, compounds with these interactions leading to linear metal chains are rather rare. Lu et al, 141 (Table 2) parallel to the a axis.…”
Section: ) Role Of Anion-mentioning
confidence: 99%
“…Ring-opening isomerism is of much current interest. Several cases have shown that reversible ring-opening of macrocyclic complexes with labile metal centers can occur in solution, and then the crystallization process can yield either the metallacycle or polymer form (often chain), which may be determined by template effects involving solvent or guest molecules, or by secondary bonding involving counterions [49][50][51][52][53][54][55][56]. However, there are remarkably few cases showing cocrystal structures of metallacycle and chain isomers [57,58].…”
Section: Metallacycles In Complexes 3-5mentioning
confidence: 99%